Faktor-Faktor Penghambat Orang Tua Siswa dalam Pembelajaran Berbasis Online di Masa Pandemi Covid 19 - Setiani, Hadijah; Adisel, Adisel; Suryati, Suryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to 1) How was the online learning process during the Covid-19 Pandemic in the social studies subject for junior high school students in RT 18 RW 04 Kelurahan Jalan Gedang, Gading Cempaka District, Bengkulu City. In an online-based learning effort during the Covid-19 Pandemic, students can carry out learning through a zoom application that uses a laptop or cellphone, junior high school students do not always learn to use the zoom application because within a day there are junior high school students working on assignments given by the teacher at the school then sends the assignment via e-mail or whatshapp message. 2) The factors inhibiting the parents of these students often occur in RT 18 RW 04 Kelurahan Jalan Gedang, Gading Cempaka District, Bengkulu City and also experienced by many other parents in other areas especially parents of students who live in areas with difficult signals. to be reached and under economic conditions. Because there are several obstacles in the learning process such as: a) The difficulty of managing time to supervise children and doing work in the office, b) There are many needs that must be fulfilled such as laptops, quotas, cell phones, c ) The limitations of parents who are teachers at home and d) Children tend to be lazy about learning. Keywords: Parents, Online Learning, Social Studies.